The effect of customer relationship management practices on airline customer loyalty - Marwa Salah; Mohamed A. Abou-Shouk (Journal of Tourism, Heritage & Services Marketing, 2019)
Customer satisfaction and loyalty are important concerns for travel providers and have a significant role in maximizing their sales. Therefore, adopting the activities of customer relationship management could help them building strong relationships with customers. This study explores the opinions of EgyptAir passengers on customer relationship management activities adopted by the company and how this affects their satisfaction and loyalty. A questionnaire was used for data collection and structural equation modelling was employed for rigorous findings. Findings revealed a positive significant effect of shared values, bonding, commitment, trust, tangibility, and handling customer conflicts on passenger satisfaction and loyalty.
Keywords: L14; L93; N37; 330; customer relationship management; Airlines; Satisfaction; loyalty